Bivalve Mollusk Paleoecology: Trophic and Environmental Reconstruction from Stable Isotopes, Sclerochronology and Shell Damage - Cintra Buenrostro, Carlos Edgar (The University of Arizona., 2006)
I examined how predatory damage in bivalve shells can be used to assess the trophic importance of species, how oxygen isotope ratios in shells can be used to estimate past salinity, and how Colorado River flow affects growth rates in a bivalve mollusk. I devised methods to distinguish predatory damage from mechanical breakage in Mytilus trossulus at Argyle Creek, Washington. After 100 h of tumbling, live-collected mussel shells were abraded and disarticulated but not otherwise damaged. Eight percent of the dead-collected shells were broken during tumbling. Three types of diagnostic damage were inflicted by crab predation in lab experiments: nibbles, nibbles and chips, and peels; and trampling and tumbling caused three types of chipping: crescentic, angular, and slivered. Crushed shells and shells with fractured margins were caused by both predation and trampling. The source of damage could be correctly identified in ~ 75% of the shells. I also investigated the trophic importance of Mulinia coloradoensis in the Colorado River Delta (CRD). I analyzed the frequency of predatory damage on shells from before the era of upstream water diversions (the "predambrian"). I documented that five to 50% of the shells were attacked by predatory gastropods or crabs. The clam's population decline probably decreased the population sizes of its predators. I also reconstructed the pristine pre-impact salinity regime of the CRD. I estimated predambrian salinities by using oxygen isotopes in shells of M. coloradoensis. Since the construction of upstream water diversions, average salinity in the estuary has increased to 38; in the predambrian, M. coloradoensis grew when salinity ranged between 22-38. I studied the growth of M. coloradoensis by examining the sclerochronology of its shell and comparing growth rates in predambrian and dambrian specimens. Each micro-growth increment in M. coloradoensis consists of two semidiurnal growth increments showing a strong fortnightly periodicity reflecting tidal cycles. In shells of similar height, predambrian M. coloradoensis shells recorded twice the number of fortnights than dambrian shells, suggesting that dambrian shells grew twice as fast as predambrian shells. The observed differences in growth rate between pre-and post-dam M. coloradoensis are probably regulated by density-dependent processes.